Viral Hepatitis in Children Unique Features and Opportunities - Jonas, Maureen M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2010)
Viral Hepatitis in Children: Unique Features and Opportunities is a unique volume that has been created to address the special considerations regarding viral hepatitis in children. It includes the latest information and recommendations specifically directed at the pediatric population, and highlights the knowledge gaps which will need to be filled to improve our understanding of these infections and treatment of this special group. Experienced practitioners from around the world have contributed these reviews, incorporating the latest studies, the current recommendations, and the distinctive pediatric issues that shape clinical care. This material will determine the research agenda for this field going forward. Viral Hepatitis in Children: Unique Features and Opportunities is a valuable resource for pediatricians, pediatric gastroenterologists, hepatologists and infectious disease specialists that care for children with viral hepatitis.
Hepatitis A in Children -- Epidemiology and Natural History of Hepatitis B in Children -- Treatment of Chronic Hepatitis B in Children -- Epidemiology and Natural History of Hepatitis C in Children -- Treatment of Chronic Hepatitis C in Children -- Hepatitis D and Hepatitis E in Children -- Hepatitis in Children due to Non-A–E Viruses -- Immunoprophylaxis of Hepatitis A and Hepatitis B in Children -- Primary Care of Children with Viral Hepatitis: Diagnosis, Monitoring, and General Management.
Keywords: Gastroenterology .; Hepatology; Pediatrics; Gastroenterology; Hepatology; Pediatrics